Um alarido neopentecostal : transversalidade e ressignificação na Igreja Universal do Reino de Deus - Bomfim, Adailson José Rosendo (2008)
This research analyzed the symbolic goods of the deriving cults of the African and spirit religions that had been remeant by the Universal Church of the Kingdom of God, after to transgress existing symbolic borders between these religiosities, causing a great howl when it offering usually these goods in the sessions of unloads and in the meetings of release , inserting itself strongly in the Brazilian religious market , so strongly marked for its pluralism. In this dispute, this church attributes to the demon the guilt of all males of the humanity, as well as it demonizes the African and spirit religiosity, as well as the Catholicism, historical Protestantism and too much religiosities. Of this form, through its rituals it obtains to Biblically legitimize to the symbolic goods of African and spirit religiosity visas as demonic, it providing to its members a new felt for the life that if it evidences through the achievement of job, marriage, health and prosperity, after a long process of release. Thus, with the charismatic leadership of Edir Macedo, the proposal Stops to Suffer and its capacity to explore the magical mentality of the Brazilian people, he obtains from a small funerary one to construct exuberant Cathedrals of Faith that it spreads in Brazil and the world, as a consequence of the pragmatism of its doctrine.